Garfield dishes it out - Davis, Jim, 1945 July 28- (New York : Random House, 1995)
Collection of black-and-white cartoon strips featuring the lazy, fat cat, Garfield.
"His 27th book"--Cover.
4.2
5-8
Keywords: Garfield (Fictitious character) -- Fiction; Cats -- Fiction; Cartoons and comics; Garfield (Fictional character) -- Fiction; Cats -- Fiction; Comic books, strips, etc